MANAJEMEN EKSTRAKURIKULER PRAMUKA UNTUK MEMBENTUK KARAKTER KEPEMIMPINAN DI SMP NEGERI 30 MUARO JAMBI - Khoirul Abdillah, Muhamad; Muspawi, Muspawi (Manajemen Pendidikan, 2023)
The large number of cases of abuse of power committed by leaders is a big challenge for future generations of the nation. Instilling leadership character in student needs to be implemented from now on. Character cultivation can be done at school, one example is by taking part in extracurricular activities in scouts. The role of scouting activities has a huge influence on the development of students' character, from discipline to love of the country. One of the schools that has implemented mandatory extracurricular activities is SMP Negeri 30 Muaro Jambi. This research intends to look for an overview of good management strategies to shape leadership character through scout extracurriculars. The research method uses qualitative research, data will be obtained descriptively. The data obtained was obtained from school principals and scout leaders as informants. Implementation was carried out from August to October, research was carried out on student activities both indoors and outdoors. Data collection was carried out by means of observation, interviews and documentation. The implementation of scout extracurricular management strategies to shape leadership character at SMP Negeri 30 Muaro Jambi goes through four stages, namely planning, organizing, implementing, supervising. The planning stage begins with recruitment by the school principal, preparing a work program, and preparing materials. Organizing is carried out by giving responsibility to the parties concerned, namely the principal, deputy principal for student affairs, homeroom teacher, and scoutmaster. Implementation is carried out once a week and the camp activity program is carried out 3 times a year. Supervision is carried out to analyze scout extracurricular activities so that the next activities will be carried out even better